Diversification strategies and equity market performances: Implications for investors and MNES. Issue 3 (2nd September 2019) - Yavas, Burhan F.; Grave, Kathleen; Vardiabasis, Demosthenes
Abstract : Purpose: This paper aims to investigate the linkages among foreign direct investment (FDI – greenfield and mergers and acquisitions [M&A]) decisions and equity market returns and volatilities. The main premise is that FDI decisions by multinational enterprises (MNE) are influenced by risk and uncertainty indicated by equity market returns and volatilities in the destination (host) countries. This is so because the events on the stock markets in general and their volatilities in particular signal the vitality of the investment climate of the target market. Understanding volatility in capital markets is important for determining the cost of capital and for evaluating direct investment and asset allocation decisions. Design/methodology/approach: Surveys and structured interviews were conducted with senior managers of 11 MNEs based in the USA to collect the data used in this study from November 2017 to October 2018. The paper investigates if FDI decisions of the MNE managers are influenced by risk and uncertainty indicated by equity market returns and volatilities. The paper endeavors to make a contribution to the IB literature in highlighting the role played by equity returns and volatilities in FDI decisions and therewith attempts to integrate finance (capital markets) with international business/strategic decision-making. Findings: Capital market performances (returns and volatilities) were found to influence the country choice for location of production facilities (FDI – both greenfield and M&A decisions) as well as timing of the FDI by a MNE. In other words, the share of production capacity optimally located abroad and M&A activities are affected by capital market returns and volatilities.